Graphene and carbon nanotube reinforced epoxy nanocomposites: A review - Singh, Navjot Pal; Gupta, V.K.; Singh, Amrinder Pal (Polymer (Guilford), 2019)
The continuous demand for low weight, economical and high strength materials have been the driving force for the search of new materials. The discovery of carbon nanofillers, viz. graphene (Ga) and carbon nanotubes (CNTs), has brought tremendous revolution in the field of epoxy-based nanocomposites. The extraordinary thermo-mechanical, electrical and flame-retardant properties offered by Ga and CNTs have led to the development of Ga/CNT-epoxy nanocomposites. The paper reviews the research conducted in the last ten years pertaining to the fabrication, characterization and applications of Ga/CNTs-epoxy composites. The major challenges faced by the researchers in developing epoxy nanocomposites for high performance applications are also highlighted. It is revealed by simultaneously reinforcing Ga and CNTs in epoxy, one could resolve major issues like poor dispersion and agglomeration of nanofillers in epoxy, which can help in developing ultra-high-performance nanocomposites. But further research is needed to explore the full potential of Ga/CNTs/epoxy hybrid nanocomposites. [Display omitted] •Ga and CNTs reinforcement in epoxy enhance thermo-mechanical properties.•Enhancement in properties is directly proportional to aspect ratio of CNTs.•Agglomeration and poor dispersion of nanoparticles are the major challenges.•Flame-retardant properties depend on integrity of the char.